Landing your first academic job: a cohort study of recent graduates from the UNC at Chapel Hill’s School of Information and Library Science - Reed, Jason; Carroll, Alexander J.; Jahre, Benjamin (My University, 2014)
The academic job market for entry level librarians remains highly competitive, and students should begin preparing themselves for the job market from the moment they are accepted into an LIS program. Lag time in selecting applicants for academic positions remains high, so students should begin the process of applying for positions well in advance of their anticipated graduation date. To prepare for this competitive job market, LIS students should expect to dedicate a significant amount of time engaging with the profession outside of the classroom, including paid LIS-related work, for-credit practicums, scholarly creativity, attending conferences, and becoming involved with professional organizations. For LIS students that supplement coursework with these activities, academic librarianship remains a viable path of employment for entry level candidates. However, job placement can remain difficult for candidates interested in very specific positions or in limited geographic areas, even for well qualified LIS graduates.
Keywords: Academic librarians; Library school students; Job placement